2015
DOI: 10.12669/pjms.315.6925
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Sepsis and its relationship with gender

Abstract: Background and Objective:Sepsis remains a leading cause of death across the world, carrying a mortality rate of 20–50%. Women have been reported to be less likely to suffer from sepsis and to have a lower risk of mortality from sepsis compared to men. The objective of this study was to determine the relationship between gender and mortality in sepsis, and compare cytokine profiles of male and female patients.Methods:This was a prospective case series on 97 patients admitted with sepsis. Clinical and microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 16 publications
3
51
1
5
Order By: Relevance
“…The incidence of sepsis is high and the mortality rate reaches nearly 20 to 50% [4]. To date, although considerable progress of anti-infective therapy and organ function support technology has been made, severe sepsis and sepsis shock are still a lethal and intractable pathological condition [5].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of sepsis is high and the mortality rate reaches nearly 20 to 50% [4]. To date, although considerable progress of anti-infective therapy and organ function support technology has been made, severe sepsis and sepsis shock are still a lethal and intractable pathological condition [5].…”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression analyses to predict 28-day mortality were performed again to derive the linear combination of the baseline model (Day 2 SOFA score) and an additional biomarker as measured based on the best time point just described. Some biomarkers were analyzed with sex as suggested in other studies [23,24]. The ROC curves were drawn and AUROC was compared between the baseline model and combination model developed with the additional biomarker.…”
Section: Resultsmentioning
confidence: 99%
“…20 In the study, age is not likely a factor correlated to the occurrence of sepsis, although study of Martin et al (2006) found those with extreme age (over 65 years) are more vulnerable to Gram-negative germs. 6 The study also showed no relationship of gender to the occurrence of sepsis, while as study of Nasir et al (2015) showed that male with sepsis had a greater chance up to 70% to death than female, as it associated with higher plasma interleukin 6 (IL-6) levels. 21 What has the study showed significantly was the correlation between blood transfusion (p = 0.0001) to IAI with OR 0.02 with 95% confidence interval, by means that transfusion has a 0.02 chance leading to sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…6 The study also showed no relationship of gender to the occurrence of sepsis, while as study of Nasir et al (2015) showed that male with sepsis had a greater chance up to 70% to death than female, as it associated with higher plasma interleukin 6 (IL-6) levels. 21 What has the study showed significantly was the correlation between blood transfusion (p = 0.0001) to IAI with OR 0.02 with 95% confidence interval, by means that transfusion has a 0.02 chance leading to sepsis. There were studies focused on the risk of bacterial contamination in preparation of hematopoietic progenitors, skin cleansing methods, changes in time of intact blood storage, cold storage of platelet suspensions, leukoreduction of red blood cells, the development of rapid screening tests for bacteria, and methods for inactivation of platelet component bacteria.…”
Section: Discussionmentioning
confidence: 98%